2022
DOI: 10.1163/09744061-bja10063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Inclusion on Credit Risk in SADC Countries

Abstract: The objective of this study is to contribute to the knowledge about the relationship between financial inclusion and credit risk in the Southern African Development Community (SADC) countries, which remains relatively unexplored in the developing countries context. The result of panel vector autoregressive models (PVAR) estimation shows that there is no bidirectional causality between financial inclusion and credit risk, but there is unidirectional causality where financial inclusion improves credit risk. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The indexes of inclusion and financial innovation are specified according to the suggestion of Jungo et al. (2019, 2022a) and are presented by the expressions (2) and (3).Where ifi is the financial inclusion index, banks is the number of bank branches per 100,000 adults, bancount is the percentage of adults over age 15 who have a bank account, save is the percentage of adults over age 15 who made savings in the past year, borrowers is the percentage of adults over age 15 who took out bank loans, deposit is the percentage of adults over age 15 who made bank deposits, withdraw is the percentage of adults over age 15 who made bank withdrawals from a financial institution, atms represents the percentage of adults over age 15 who used ATMs to make payments or withdrawals and WJs are the weights of the respective coefficients.Where innov is the financial innovation index, WPs…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indexes of inclusion and financial innovation are specified according to the suggestion of Jungo et al. (2019, 2022a) and are presented by the expressions (2) and (3).Where ifi is the financial inclusion index, banks is the number of bank branches per 100,000 adults, bancount is the percentage of adults over age 15 who have a bank account, save is the percentage of adults over age 15 who made savings in the past year, borrowers is the percentage of adults over age 15 who took out bank loans, deposit is the percentage of adults over age 15 who made bank deposits, withdraw is the percentage of adults over age 15 who made bank withdrawals from a financial institution, atms represents the percentage of adults over age 15 who used ATMs to make payments or withdrawals and WJs are the weights of the respective coefficients.Where innov is the financial innovation index, WPs…”
Section: Methodsmentioning
confidence: 99%
“…The indexes of inclusion and financial innovation are specified according to the suggestion of Jungo et al (2019Jungo et al ( , 2022a and are presented by the expressions (2) and (3).…”
Section: Controlling Corruption Inmentioning
confidence: 99%
“…These measures are diverse and include various changes in regulatory requirements that banks are required to comply. These regulatory measures include higher capital adequacy requirements (Jungo et al , 2022; Ezeocha, 2020), countercyclical provisioning, as well as liquidity risk and leverage management (Kuo et al , 2022; Prasad, 2010).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The effects of reforms on banking sector’s financial and regulatory performance, as well as on the economy, according to evidence by different studies, have been varied. Some studies find that banking reforms improve the sector’s financial and operational performance in terms of better returns, productivity and efficiency (Ezeocha, 2020; Olajide et al , 2011; Zhao et al , 2010; Adegbaju and Olokoyo, 2008; Brissimis et al , 2008; Angelini and Cetorelli, 2003), financial system stability (Jungo et al , 2022; Kuo et al , 2022) and thus support economic growth and development (Boikos et al , 2021), while some others could not establish any positive linkage between reforms and performance (Okpara, 2011; Das and Ghosh, 2006; Fernandez De Guevara et al , 2005; Maudos and Fernandez De Guevara, 2004; Kumbhakar and Sarkar, 2003).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…One strand of literature highlights a potential positive relationship between financial inclusion and bank credit risk. Jungo et al (2022) found that higher levels of financial inclusion in rural areas in Uganda could result in increased credit risk for banks. The authors attribute this finding to policymakers' emphasis on increasing bank credit to meet political demands, potentially leading to insufficient consideration of the financial skills and repayment abilities of newly included individuals and ultimately increasing credit risk.…”
Section: Impact Of Financial Inclusion On Bank Credit Riskmentioning
confidence: 99%